Analysis of Online Learning Impact of the Covid-19 Pandemic from the Perspective of Biology Educators - Maesaroh Maesaroh; Devi Anugrah; Mega Elvianasti; Irdalisa Irdalisa (Jurnal Pendidikan Biologi, 2021)
The physical distancing policy implemented by the government prohibits physical meetings to prevent the spread of the Covid-19 virus including all activities in the educational process. The online learning system is implemented to facilitate teaching and learning activities without physical meetings between lecturers and students. This study aims to analyze online learning from the perspective of the lecturers biology education departement in courses based on pedagogical competences and scientific work skills or practicum activity. Surveys and interviews were used to obtain data with a quantitative approach. The results of the study provide information that:1) online learning still allows interactive activities in class; 2) online learning platforms are used in an integrated by lecturers; 3) WhatsApp Zoom and Google Meet are the most widely used platforms because they support synchronous and asynchronous learning; 4) practical activities are carried out using materials available at students' homes and with the help of practical tutorial videos from lecturers and virtual laboratories. Through the full online learning system for even one semester the lecturers of the biology education departement have carried out the learning process well by always providing feedback and the interactive learning between students and lecturers online with the help of various learning platforms. This study provides information about the information of full online leraning at university.